2013
DOI: 10.1111/jfpp.12168
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Heat and Mass Transfer during Frying of Gulab Jamun

Abstract: Mathematical models were developed for the heat and mass transfer phenomena during deep‐fat frying of gulab jamun, a dairy dessert popular throughout the Indian subcontinent. Size, shape, core temperature, moisture and fat contents of the product were monitored at regular intervals during 8 min of frying. The heat transfer was described using both lumped capacity model and transient heat conduction equation. As the calculated Biot number for lumped capacity model was greater than 0.1, the convective heat trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…The authors also stated that the fat content was not directly related to frying temperature itself, but was rather closely associated with the final moisture content, which was, in turn, affected by temperature. The fat content of Gulabjamun obtained for both the frying processes inversely related to its moisture content which was in agreement to the trend reported by Franklin et al (2013).…”
Section: Oil Uptakesupporting
confidence: 91%
“…The authors also stated that the fat content was not directly related to frying temperature itself, but was rather closely associated with the final moisture content, which was, in turn, affected by temperature. The fat content of Gulabjamun obtained for both the frying processes inversely related to its moisture content which was in agreement to the trend reported by Franklin et al (2013).…”
Section: Oil Uptakesupporting
confidence: 91%
“…), 90‐130 W/(m 2 K) for gulabjamun (Franklin et al . ). The heat transfer coefficient values for other food products are 208–331 W/(m 2 K) for chicken strips (Velez‐Ruiz et al .…”
Section: Resultsmentioning
confidence: 97%
“…For comparison, the Biot number for gulab jamun was reported to range between 0.49 and 0.61 (Franklin et al . ). Since the calculated Biot numbers were greater than 0.1, it could be concluded that the lumped thermal capacity model was not suitable (Incropera and Dewitt ; Kumar ) for determination of the heat transfer coefficient of pantoa during DFF.…”
Section: Resultsmentioning
confidence: 97%
“…), gulabjamun (Franklin et al . ), etc. Similarly, studies on porosity changes in various products during frying exist (Krokida et al .…”
Section: Introductionmentioning
confidence: 99%